Implementation of individual investment choice in a public service defined contribution pension fund - Robinson, Colleen Heather (My University, 2014)
This report focuses on trends which have occurred internationally and nationally within the retirement fund arena. Various forms of funds i.e. defined benefit (DB) or defined contribution (DC), as well as the possibility of the implementation of individual member investment choice (MIC), are explored within private, parastatal and public sector funds. Case studies are used to illustrate the problems, successes and failures experienced with the conversion process and implementation of MIC. All of the above areas were analysed in order to propose an optimal solution for public sector retirement funding within South Africa. The report concludes that a dual approach is required. It is proposed, that the Government Employees’ Pension Fund remain a DB fund in the short to medium term, while various forms of modernization occur in order to bring the fund in line with the requirements of the Pension Funds Act as well as to reduce the financial burden on. the State. For local government retirement funding, the evidence is inconclusive and an optimal solution can therefore not be proposed at this stage. Recommendations are however made as to the process to be followed in order to introduce a sense of urgency into the matter of finalizing the debate on the optimal future state for local government retirement funding.